Needs analysis and design of an interactive learning video on Indonesian traditional dance for senior high school students - Pratiwi, Stefi Winda; Yetti, Elindra; Rakhman, Rizki Taufik (FBSB UNY, 2025)
Dance learning in high schools is dominated by conventional methods of memorizing movements, while critical thinking and art appreciation aspects are less considered. This study aims to analyze the needs and design a prototype of an interactive learning video based on Indonesian traditional dance to improve students' critical thinking skills and dance appreciation. Using Research and Development (R&D) approach with the ADDIE model in the initial stage (Analyze and Design). Data were collected through observation, teacher interviews, student questionnaires, and a pretest administered to 36 grade 10 students in public high schools in Jakarta. The needs analysis revealed that teachers primarily used PowerPoint, resulting in students being passive and struggling to understand the meaning of dance symbols. The student questionnaire confirmed that most preferred visual and interactive learning media to help understand cultural symbols in dance. The pretest results also showed that students had low initial abilities in interpreting the meanings of movements, symbols, and aesthetic elements of dance. Based on these findings, an interactive learning video was designed to serve as the primary contextual and interactive learning medium, integrating critical thinking and appreciation skills in dance education for high schools.